Avaliação do processo de transporte neonatal inter-hospitalar de uma maternidade escola - Souza, Emeline Noronha Vilar de (2019)
Neonatal transport consists of the transfer of a newborn to a more specialized unit. The same can be classified as intrahospital and interhospital. It is believed that the conditions of the inter-hospital transfer influence neonatal mortality, so when performed ideally, it should contribute to the reduction of neonatal and infant mortality rates. One of the great advances of Neonatology was the implantation of Neonatal Transportation, which effectively contributed to the reduction of neonatal and infant mortality rates. There is also a gap in the literature regarding interhospital transport coming from a team trained by the institution, being one of the pillars for the accomplishment of this study. The objective of this study was to evaluate the quality of the inter-hospital neonatal transport of a Maternity school through the Ca-TRIPS score. This is a cross-sectional, descriptive, observational study with a quantitative approach. The data collected were inserted into a form, after which a bivariate analysis of the data was performed, in which the association of the selected independent variables was verified, all of which were related to the profile of the NB transported and characteristics of the transport (duration and demanding sector) with the dependent variable (inadequate transport). At the time of analysis, their respective prevalence ratios (PR) were estimated, using poisson regression with robust variance, also used in the multiple analysis. In the intermediate model, the variables that had a value of p <0.20, obtained in the bivariate analysis, were initially considered and remained in the final model if p <0.05. It was developed in a Reference Maternity School in Rio Grande do Norte. The sample consisted of 70 inter-hospital neonatal transports performed by professionals and residents of the institution from May to October 2018. It resulted in: performed 70 interhospital transports, of these 71.4% were considered adequate, Female predominance (62.9%), birth weight below 2,500 g (62.9%) and preterm gestational age (55.7%). The median of the duration of transport was 40 minutes with some mechanical failures. Most of the transports (37.1%) were to perform exams and the most present sector of origin was the Neonatal ICU (61.4%), 90% of the transports were made with venous access and 55.7% ambient air. It was identified that the lower birth weight of the newborn and/or longer of the transport duration, the greater the prevalence of inadequate transport. A specialized team contributes significantly to the quality of transportation. The study showed that inter-hospital neonatal transport was adequate in most transports according to the Ca-TRIPS score.